Pengaruh Rotasi Tanaman Terhadap Kualitas Fisik Tanah Dan Efesiensi Penggunaan Air - Dohona, Nurul Hamidah; Halawa, Herni Jelita (CV. SINAR HOWUHOWU, 2024)
This study aims to evaluate the effects of crop rotation on soil quality and water use efficiency in Gunungsitoli. The method used was a Randomized Complete Block Design (RCBD) with treatments consisting of monoculture and crop rotation systems. Data were collected from soil pH analysis, organic matter content, nutrient levels (N, P, K), and measurements of water use efficiency during the growth period. The results indicated that crop rotation significantly improved soil pH, organic matter content, and water use efficiency compared to the monoculture system. The implementation of crop rotation proved effective in enhancing soil quality and supporting sustainable agricultural practices. This study recommends crop rotation as a strategy to boost agricultural productivity and preserve natural resources.